O Programa Executivo Bolsa-Escola no município de São José do Rio Preto: uma proposta de universalização da educação ou de transferência de renda? - Durigan, Adriana Nominato do Amaral (2006)
The low income of the illiterate population in Brazil was for a long time pointed as a consequence of its educational situation and cause of a gap between the highly sophisticated work market and a non qualified hand labor. The State, aiming to correct this disproportion through education, has started to create opportunities of access to education, targeting a better social justice level. The minimum income projects monetary help were not originally linked to the education. They used to target an income universal allocation in order to face unemployment and poverty. With time, the minimum income programs in Brazil have restricted the benefits supply to the families which had children in school age. The link between income and education was incorporated in order to join the idea that the State could not only furnish the benefit without no the beneficiary to learn anything from the process, as a counterpart. Besides that, that would be a way to make the education universal right possible, as it is determined by the Human Rights Declaration, Constitution, BDL and CTA. In São José do Rio Preto, one of the São Paulo State cities with better HDR (Human Development Rate) (0,834) and educational coverage in the country, the introduction of the School Fund Program had as its basis the same principles as the Federal Government School Fund Executive Program. The research evaluates and concludes the lack of any kind of special attendance to the families helped and the control, restricted only to the observing of the children frequency to school. Finally, through a questionnaire applied to the students, parents and teachers from Darcy Ribeiro City School and to the City Education Secretary we have evaluated the children school development before and after receiving the Fund, besides the idea the Education Secretary has towards the Program.